Electrostatic flocking MnO2 nanofiber electrode for long cycling stability supercapacitors. (10th February 2022) - Li, Mengru; Qin, Liming; Ou, KangTai; Xiong, Zhiyuan; Zheng, Hengyu; Sun, Youyi
Summary: A new double‐layer hybrid electrode based on MnO2 nanofibers was prepared by the electrostatic flocking method. Compared with the traditional dopping method, the MnO2 nanofibers can be embedded on surface of graphene/polyvinylidene fluoride (PVDF) composite coating. The symmetrical supercapacitor based on electrostatic flocking electrode was further assembled, which showed a high energy density of 12.1 Wh kg −1 and ultra‐long cyclic life of 109.4% after 10 000 cycles. The result was attributed to that electrostatic flocking MnO2 nanofibers were directly exposed to electrolyte, reducing interfacial resistance. The work provides a new way to prepare high‐performance electrode for various applications. Abstract : A new double‐layer hybrid electrode based on MnO2 nanofibers was developed. The electrode was prepared by electrostatic flocking method. The electrode exhibited excellent electrochemical stability.